(untitled) (Global Journal of Human-Social Science, 2020)
The Far Eastern Federal District of Russia is the largest by area (40.6% of its territory), but the most sparsely populated (5.57% of the population) and economically inactive. At the same time, the number of residents of the District continues to decline. The main reason for the observed quantitative losses is the outflow of the population in the form of the so-called "Western migration drift." The resulting demographic "vacuum" of the Far Eastern Federal district looks increasingly alarming against the background of very high demographic pressure on the adjacent territories of Russia’s Asian neighbors. The development of problematic territories always requires significant investments in human capital. For sustainable development of the region and adequate realization of human capital, it is necessary to create appropriate institutional conditions. According to the decision of the Russian Government, one of them is a mechanism for attracting labor resources to the Far East through the free provision of land plots called "Far Eastern Hectare" (FE-hectare). The article critically analyzes the implementation of this law.